The Association Between Gastrointestinal Symptoms and Transvaginal Ultrasound Findings in Women Referred for Endometriosis Evaluation: A Prospective Pilot Study - Cohen Ben-Meir, Lee; Soriano, David; Zajicek, Michal; Yulzari, Vered; Bouaziz, Jerome; Beer-Gabel, Marc; Eisenberg, Vered H. (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose To evaluate the relationship between gastrointestinal (GI) symptoms and transvaginal ultrasound (TVUS) findings suggestive of endometriosis.Materials and Methods A prospective design. Women referred for a diagnostic ultrasound due to suspicion of endometriosis completed a Rome III and Pelvic Floor Distress Inventory (PFDI-20) questionnaire for clinical, GI symptoms, before undergoing TVUS. Endometriosis was diagnosed in the presence of endometriomas and/or deeply infiltrative endometriotic (DIE) lesions. Association between lesion sites and GI symptoms was evaluated by univariate and multivariate analysis.Results The study included 241 women who presented with: dysmenorrhea (89.6 %), dyspareunia (76.3 %), chronic pelvic pain (77.2 %), dyschezia (66 %), hematochezia (15.4 %), subfertility (24.5 %). GI symptoms were present in 25.3–76.8 % and 5.4–55.6 % of Rome III and PFDI-20 questionnaire responses, respectively. TVUS findings were endometriomas (23.2 %), peritoneal adhesions (46.5 %), uterosacral ligament (26.7 %), retrocervical (11.2 %), rectosigmoid (11.2 %), intestinal (4.6 %), and bladder (0.8 %) involvement, and pouch of Douglas (POD) obliteration (15.4 %). There was a high prevalence of peritoneal adhesions, uterosacral ligament involvement, and rectosigmoid and intestinal nodules on TVUS in women with GI symptoms, up to Chi2 = 9.639 (p = 0.013) on univariate and Chi2 = 8.102 (p = 0.005) on multivariate analysis.Conclusion We observed an almost 10-fold increase in DIE lesions in women with GI symptoms. We suggest that the presence of GI symptoms should prompt a referral for endometriosis evaluation and performance of a dedicated TVUS before invasive gastrointestinal procedures.
Keywords: endometriosis; ROME 3; noninvasive imaging; gastrointestinal symptoms; transvaginal ultrasound